PENDIDIKAN ISLAM MULTIKULTURAL DAN DERADIKALISASI DI KALANGAN MAHASISWA - Supardi, Supardi (Analisis: Jurnal Studi Keislaman, 2013)
This study aims to describe the level of multicultural education and deradicalization,  and analyze the influence of Islamic education multicultural to de-radicalization  of religion. The research was conducted students  of teaching primary Faculty Eduacation  and Teaching IAIN SMH Banten. The methodology used is quantitative correlation;  using a Likert  scale questionnaire  with five choice. The results show: First, the level multicutural  Islamic education and de-radicalization  of the religion were high and satisfactory. Secondly  there  is positive  and significant  multicultural Islamic education    to   the   deradicalization   of   religion   among   the students. The influence of multicultural Islamic education to de- radicalization of religion by 39.69 %. The higher the multicultural education Islamic the higher the de-radicalization of religion. De- radicalization  of religion on students  can be improved  through multicultural islamic education.  Therefore the university  should implement multiculturalism in all aspects of campus life that de- radicalization  religion among students higher.